District School #3: Alma, KS (1893-1925): A Case Study of Integrated Schooling - Schendt, Jamie (Kansas State University. Dept. of History. Chapman Center for Rural Studies, 2010)
Jamie Schendt writes a history of Bean School (District #3 one room school) in Wabaunsee County. Serving an integrated landscape of both white and African American farmers, Bean School was attended by Washington Owen, first black graduate of KSU. The author shows that Bean school played many roles in the community, including a shared Bible Study forum sometimes led by African American farmers. Early photographs of the school and plat maps are included.
Keywords: African American; Wabaunsee County; One-room schools; Washington Owen